2022
DOI: 10.1177/20436106221075636
|View full text |Cite
|
Sign up to set email alerts
|

Residential homes for children in Ghana: Compliance with standards, quality of care, and case management

Abstract: Accurate data on the extent to which residential homes for children in Ghana are in compliance with national standards for quality of care and case management are lacking. To begin to address this gap, a census of residential homes and an enumeration of the child population were undertaken in 2019, followed by a survey on a representative sample of children living in such homes. Data were gathered on the types and characteristics of all 139 residential homes operating in the country at the time and the demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In addition, many studies with a focus on national childcare reforms mention the importance of international influences. For example, national reforms of childcare deinstitutionalization are often associated with globally spreading deinstitutionalization ideas and the institutions-as-a-last-resort rhetoric (Bindman et al, 2019; Huseynli 2018; James et al, 2021; Petrowski et al, 2022), as well as ‘harder’ economic and political influences of external actors, e.g. through budget support programmes and EU accession leverage (Greenberg and Partskhaladze 2014; Iusmen and Stalford 2015; Ulybina, 2020).…”
Section: Looking At Child Institutionalization Through the Lens Of Gl...mentioning
confidence: 99%
“…In addition, many studies with a focus on national childcare reforms mention the importance of international influences. For example, national reforms of childcare deinstitutionalization are often associated with globally spreading deinstitutionalization ideas and the institutions-as-a-last-resort rhetoric (Bindman et al, 2019; Huseynli 2018; James et al, 2021; Petrowski et al, 2022), as well as ‘harder’ economic and political influences of external actors, e.g. through budget support programmes and EU accession leverage (Greenberg and Partskhaladze 2014; Iusmen and Stalford 2015; Ulybina, 2020).…”
Section: Looking At Child Institutionalization Through the Lens Of Gl...mentioning
confidence: 99%
“…A lack of investment in alternative care, as well as infrastructure to support and oversee these placements, frequently contributes to these difficulties (Petrowski et al, 2022). Examples from some post-Soviet LMICs have, however, demonstrated that funding availability can be a significant enabler of DI efforts (Greenberg & Partskhaladze, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both emphasise the importance of social workers who can support children through clear case management processes, as well as highlighting the varied and complex experiences and relationships of children in residential care leading to varied outcomes. Petrowski et al (2022) remind us that data on numbers of children who are separated from their families, and on their wellbeing, is critical to inform policy and practice. Findings are reported on residential care in Ghana from a two-stage survey to track the number of residential care providers and the number of children in their care, as well as the wellbeing of the children.…”
Section: Contributions To the Themed Editionmentioning
confidence: 99%
“…Other examples of methodologies closely linked to practice come from care reform efforts in Ghana. The first (Cappa et al, 2022), draws from a large survey of residential care providers and the second (Frimpong-Manso et al, 2022) presents findings from a quantitative analysis of interview data with 408 children. These more quantitative pieces of data collection are helpful in providing high level results on the general situation of the provision of alternative care in the country.…”
Section: Contributions To the Themed Editionmentioning
confidence: 99%
See 1 more Smart Citation